Implementation of the 7P Marketing Mix Principles as a Marketing Strategy for Business People: Application to the Business Community of KP. Ambon CU. Hati Amboina, Ambon, Indonesia - Tabelessy, Walter; Ralahallo, Fransiska Natalia; Loppies, Lilian Sonya; Pattinaja, Elna Marsye; Siahaan, Martha Herlina (Indonesian Community Empowerment Journal, 2023)
Using the 7P marketing mix principles is becoming increasingly important. By combining these seven elements, the business community of KP. Ambon CU. Hati Amboina can create a holistic marketing strategy which focuses not only on product and price but also on customer experience, efficient business processes, and impressive physical evidence. This activity is an implementation of the 7P marketing mix principles in the context of the business community of KP. Ambon CU. Hati Amboina, Ambon, Indonesia. This activity presents how the business community can utilize each element in the 7Ps to improve their marketing strategies, address local challenges, and build stronger relationships with customers. Community service activities are carried out in the form of workshops and discussions. Community service activities are carried out by first carrying out an initial discussion process regarding understanding the business community of KP. Ambon CU. Hati Amboina, Ambon, Indonesia, is related to marketing capabilities based on the 7P principles and accommodating the aspirations of the business community regarding matters they wish to discuss regarding marketing capabilities based on the 7P principles of the business community of KP. Ambon CU. Hati Amboina, Ambon Indonesia. This community service activity is quite effective in increasing the knowledge aspect of the business community of KP. Ambon CU. Hati Amboina is related to the 7P marketing principles. The increase in knowledge score from an average of 47.86 to 88.35 shows the effectiveness of community service activities in implementing the 7P marketing principles through workshops and discussions.